Integrating Challenge-Based-Learning, Project-Based-Learning, and Computer-Aided Technologies into Industrial Engineering Teaching: Towards a Sustainable Development Framework - Roberto Pérez-Rodríguez; Rafael Lorenzo-Martin; Carlos A. Trinchet-Varela; Rolando E. Simeón-Monet; Jhonattan Miranda; Daniel Cortés; Arturo Molina (National Research Mordova State University, 2022)
Introduction. Teaching industrial engineering in the second decade of the 21st century requires problem-solving and decision-making competencies oriented towards sustainable development. The growth of information metrics, the Internet of Things, virtual and augmented reality, and Artificial Intelligence bring more diverse, complex and imprecise challenges. This article aims to show a framework employing Challenge-based-learning, Project-based-learning and Computer-Aided technologies as dynamic resources supporting the comprehensive teaching of industrial engineers for industrial solutions oriented towards sustainable development. Materials and Methods. Our research involved a systemic analysis of the framework variables, the stages, and the partial results of its application in three academic years research. We selected several case studies to evaluate the professional competencies related to Sustainable Development Goals of industrial engineering students, using active learning tools integrated with Computer-Aided technologies. These cases illustrated the acquisition of Sustainable Development Goals competencies. Two simultaneous Latin American scenarios were examined (Mexico and Cuba). Results. Its main contribution is an appropriate framework for using Challenge-based-learning, Project-based-learning and Computer-Aided technologies as resources to develop professional competencies in industrial engineering and sustainable development. The control groups results demonstrate the utility, relevance, and accuracy of the proposed framework. Results. Its main contribution is an appropriate framework for using Challenge-based-learning, Project-based-learning and Computer-Aided technologies as resources to develop professional competencies in industrial engineering and sustainable development. The control groups results demonstrate the utility, relevance, and accuracy of the proposed framework. Discussion and Conclusion. The study of the theoretical and methodological components of teaching Industrial Engineering, emphasizing competencies, at two universities in Latin American countries revealed the need to understand Computer-Aided technologies as a complex process. The proposed framework considers Computer-Aided technologies per the typologies of selected competencies integrated into the curricular design, including Challenge-based-learning and Project-based-learning, oriented toward the Sustainable Development Goals. The authors' conclusions contribute to the development of active learning methods in engineering, supported by the application of CAD/CAM/CAE tools and focused on the fulfillment of sustainable development objectives. The materials of the article will be useful for the teaching of Industrial Engineering from a digital transformation perspective, contextualized in sustainable development environments.